High-resolution analysis of life-cycle carbon emissions from China's coal-fired power industry: A provincial perspective. (September 2020) - Li, Junjie; Wang, Yonggang; Xu, Deping; Xie, Kechang
Highlights: The information data of 99.7 % and operation data of 47.8 % of all coal-fired power units in China are investigated. Carbon emission factors of 22 coal-fired power technologies and technology structures of 30 provinces is considered. High-resolution carbon emissions from the coal-fired power industry at the province-level are estimated. The carbon reduction potential caused by technology structure optimization and energy conservation is analyzed. Abstract: The expansion of China's coal-fired power industry is facing enormous pressure to reduce carbon emissions in the context of global decarbonization. Existing national-level carbon accounting is insufficient to support developing carbon reduction policies and measures tailored for specific locations. In this study, we conducted a spatially high-resolution analysis to estimate life-cycle carbon emissions from the coal-fired power industry at the province-level. The estimate is from a bottom-up perspective, including computing carbon emission factors for 22 coal-fired power technologies based on the operation data of 47.8 % of all units, measuring provincial technology structures based on the information data of 99.7 % of all ones, and weighted calculating the above two terms. We also analyzed the carbon reduction potential of the coal-fired power industry according to relevant measures by province. The estimate shows great differences in carbon emission factors of various technologies. The coupling of these factors with different technology structures causes significant variations of 0.933–1.019 kg CO2 eq/kWh in the carbon emission factors of the coal-fired power industry at the province-level. In 2016, carbon emissions from China's coal-fired power industry were 3835 Mt CO2 eq and intensive in the northern and eastern provinces. From 2016 to 2020, carbon emission factors in most provinces will decrease by 3 %–6 % benefiting from technology structure optimization and energy conservation. The falling of carbon emission factors leads to a carbon reduction potential of 307 Mt CO2 eq in total. In particular, Beijing and Shandong achieve negative growth in carbon emissions from the coal-fired power industry during this period.